2014
DOI: 10.1111/1574-6968.12613
|View full text |Cite
|
Sign up to set email alerts
|

Putrescine controls the formation ofEscherichia colipersister cells tolerant to aminoglycoside netilmicin

Abstract: Persisters are suggested to be the products of a phenotypic variability that are quasi-dormant forms of regular bacterial cells highly tolerant to antibiotics. Our previous investigations revealed that a decrease in antibiotic tolerance of Escherichia coli cells could be reached through the inhibition of key enzymes of polyamine synthesis (putrescine, spermidine). We therefore assumed that polyamines could be involved in persister cell formation. Data obtained in our experiments with the polyamine-deficient E.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
20
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 27 publications
2
20
0
3
Order By: Relevance
“…Control experiments showed no differences among the three strains when exposed to ciprofloxacin (Fig. 5C), in agreement with previous findings (34,35).…”
Section: Phop Promotes Antibiotic Persistence By Stabilizing the Clpssupporting
confidence: 92%
See 2 more Smart Citations
“…Control experiments showed no differences among the three strains when exposed to ciprofloxacin (Fig. 5C), in agreement with previous findings (34,35).…”
Section: Phop Promotes Antibiotic Persistence By Stabilizing the Clpssupporting
confidence: 92%
“…Oat and the ClpXP Substrate RpoS. Putrescine is required for persistence toward aminoglycoside antibiotics in E. coli (34,35). In Pseudomonas aeruginosa, inactivation of the putrescine aminotransferase gene spuC (a homolog of the Salmonella oat gene) reduces persister formation (36).…”
Section: Phop Promotes Antibiotic Persistence By Stabilizing the Clpsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because some of the strains used in the literature, including those used to develop the concept of a polyamine modulon (MA261) (59) contain an amber mutation in codon 33, further work is needed to determine which strains have this amber mutation and to evaluate whether the effect of added polyamines is solely the result of read-through of such an amber mutation. Thus, Tkachenko et al (60) in their studies on bacterial persister cells specifically showed that putrescine increased RpoS levels both in rpoS amber and non-amber cells.…”
Section: Discussionmentioning
confidence: 98%
“…Clinically, persisters have been found to be important to the pathogenesis of infections, including persistent tuberculosis, reoccurring uropathogenic E. coli infections, and Pseudomonas aeruginosa infections in cystic fibrosis patients (10)(11)(12)(13)(14). The rate of persister formation is much higher in stationary-phase cells than in actively growing cells (10,(15)(16)(17)(18)(19). In addition to increasing rates of persister formation, stationary phase can also increase rates of resistance and tolerance to antibiotics (18,(20)(21)(22)(23).…”
mentioning
confidence: 99%